A influência da idade de aquisição e da proficiência no processo de acomodação sintática de passivas por bilíngues português-inglês - Glenday, Candice Helen (2020)
The aim of this study was to investigate syntactic processing of passive sentences in English by Brazilian Portuguese learners of English as a second language (ESL) with intermediate and advanced proficiency levels and different ages of L2 acquisition. The general objective of the dissertation was to verify to what extent their mother tongue (Brazilian Portuguese) would influence the understanding and production of passive sentences in English with two-argument and three-argument verbs. Thus, a translation task and a self-paced reading task were developed to investigate the syntactic processing of passive sentences by two groups (intermediate and advanced) of university English learners. In addition to these tasks, the Vocabulary Size Test (VST) was administered to assess the participants’ level of proficiency. Based on the quantitative and qualitative analysis of the data obtained from the two tasks, the results were related to the participants' age acquisition and proficiency levels. The results of the self-paced reading task revealed that the reading time was longer in participants in the intermediate group who acquired English after the age of 16 years (AoA3) when compared with those who acquired English between the ages of 12-16 years (AoA2). In the advanced group, the reading time of the segments was progressively longer in participants who acquired English at the ages of 1-11 years, 12-16 years and after the age of 16 (AoA1, AoA2 and AoA3, respectively). Late learners, those who acquired the L2 after the age of 16 (AoA3), tend to use their syntactic knowledge of L1 (mother tongue) during the production and comprehension of passive sentences in English (L2). The results obtained from the translation task suggest that the process of syntactic overlapping was evident in both groups and at different levels of proficiency.